Brechas tecnológicas, enseñanza remota y repercusiones en el aprendizaje: El testimonio de estudiantes universitarios sobre su aprendizaje durante la pandemia (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This work is the result of a research project whose purpose was to identify the impact of technological gaps on student learning during the COVID-19 pandemic. A mixed sequential analysis study was carried out in two phases. In the first phase, from a quantitative approach, surveys were applied to 131 students from a public university in Mexico to identify different profiles of technological qualification. In the second phase, from a qualitative approach, the technological qualification profiles of 10 students were analyzed in depth, to contrast them with the learning obtained during the pandemic; To this end, interviews were conducted in which the content analysis technique was subsequently applied. The results indicate that students with insufficient technological qualification profile show greater gaps in their learning, in contrast to students who have sufficient technological resources. However, regardless of the technological profile, all the students presented difficulties, to a greater or lesser extent, in continuing their studies remotely. In fact, some cases refer to students who, despite having computer equipment, a good internet connection and adequate spaces to work at home, show a reduction in their learning. It is concluded that the technological room has not been sufficient to achieve the expected learning during the emergency remote modality, due to the fact that there is a third-level digital gap related to the effective appropriation of technological resources for teaching and learning. In this sense, digital literacy is a pressing need, both in the training of future generations of students and in the training of teachers.